2013
DOI: 10.1523/jneurosci.4369-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Synchronous Activity of Lateral Habenular Neurons Is Essential for Regulating Hippocampal Theta Oscillation

Abstract: Lateral habenula (LHb) has attracted growing interest as a regulator of serotonergic and dopaminergic neurons in the CNS. However, it remains unclear how the LHb modulates brain states in animals. To identify the neural substrates that are under the influence of LHb regulation, we examined the effects of rat LHb lesions on the hippocampal oscillatory activity associated with the transition of brain states. Our results showed that the LHb lesion shortened the theta activity duration both in anesthetized and sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 72 publications
5
74
0
1
Order By: Relevance
“…Memory formation and retrieval depend upon the HPC (D'Hooge and De Deyn, 2001), and more specifically upon the presence of theta oscillations within the dHPC (Düzel et al, 2010). A high degree of synchrony between LHb and dHPC theta oscillations has recently been demonstrated (Aizawa et al, 2013b;Goutagny et al, 2013). Moreover, we have shown that spatial memory performance was positively correlated with theta coherence between the LHb and the dHPC (Goutagny et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Memory formation and retrieval depend upon the HPC (D'Hooge and De Deyn, 2001), and more specifically upon the presence of theta oscillations within the dHPC (Düzel et al, 2010). A high degree of synchrony between LHb and dHPC theta oscillations has recently been demonstrated (Aizawa et al, 2013b;Goutagny et al, 2013). Moreover, we have shown that spatial memory performance was positively correlated with theta coherence between the LHb and the dHPC (Goutagny et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
“…We have shown that electrolytic habenular lesion altered hippocampus (HPC)-dependent spatial learning in the water maze (WM) (Lecourtier et al, 2004), whereas selective LHb inactivation induced memory deficits in an object-based, HPC-dependent memory task (Goutagny et al, 2013). Moreover, a high synchrony between LHb and dorsal HPC (dHPC) theta oscillations has been evidenced (Aizawa et al, 2013b;Goutagny et al, 2013). On the basis of the well-accepted view that communication between regions involves coherence of their oscillations (Fries, 2005), these data suggest that the LHb and dHPC are functionally connected and are likely to exchange information.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that LHb lesions reduced the duration of REM sleep, an effect that depended on the activity of serotonergic neurons in the median raphe nucleus (MRN) [83]. Serotonin is known to play a critical role in the regulation of REM sleep by preventing pontine cholinergic systems from triggering REM onset [84].…”
Section: Sleep and Circadian Rhythmsmentioning
confidence: 99%
“…Nedavna istraživanja potvrdila su pretpostavke da patološki izmenjena aktivnost neurona lHb utiče na razvoj simptoma depresije, kao što su pad raspoloženja (43,44), nemogućnost uživanja (45) i poremećaj sna (46). Smatra se da stresna stanja povećavaju nivo bazalne aktivnosti neurona lHb, što dovodi do kontinuirane inhibicije aktivnosti dopaminergičkih neurona mezencefalona i posledično, do smanjenja motorne aktivosti i motivacije (27,47), kao i do inhibicije serotinergičkih neurona nc.…”
Section: Kontrola Sistema Zadovoljstva I Motornog Odgovoraunclassified